PENGARUH SHORT MESSAGE SERVICE (SMS) TERHADAP MINAT BELI KONSUMEN PADA PT ISTANA KENCANA MOTOR BATAM - Rika Harman (Universitas Putera Batam, 2013)
Nowadays, Short message services (SMS) is a popular public service which is offered by the provider of mobile phone. SMS is used as a tool of communication for users, even more, it is frequently used to promote the products of company, send information/ messages to partners and friends. This research is conducted in PT Istana Kencana Motor which is used to find out the influences between SMS toward the costumers’ purchasing interest. It is interesting and need to be explored in considering the use of mobile phone, the providers who offers some facilities to the costumers, and the need of economical transportation, in this case, motorcycle. The sample of the research is the costumers of PT Istana Kencana Motor. The technique of data analysis was using SPSS. The result of the research is hoped to be useful for PT Istana Kencana Motor in considering better decisions in finding out the costumers’ demanding and complaining.